An environmental quality management scheme for Canlubang New City - Gemanil, Editha M.
The environmental quality management of a project area like the Canlubang New City encompasses a big sphere of activity. This may be basically defined as an influencing of human activities as they affect the quality of mankind's physical environment especially the air, water and terrestrial features. This environmental management takes sanitary engineering, environmental health, urban and regional planing and public administration in totality. The concern of this study is to encompass overall environmental quality management planning; considering that environment has a four-fold implication. The first concept considers all natural aspects of the environment like air, noise, sewage, solid wastes, toxic substances, and water. The second definition however, encompasses energy, historical preservation, land use, open space, radiation, population and wildlife preservation; while the third implication covers aesthetics, health, housing, mass transportation, recreation, streets and housing. The fourth implication being the broader is also of relevance to this research study, which considers economic development, education, employment, public safety and welfare. These concepts are conceived in the proposed environmental quality management of the Canlubang New City.